Political Economy and contemporary Renaissance - Ângela Lacerda-Nobre; Amandine Gameiro; Rogério Duarte; Marc Jacquinet; Rafael Pérez (Cidades, Comunidades e Território, 2023)
In times of severe crisis there are emergence phenomena, which are characterized by disruptive rethinking of previous, taken for granted assumptions. The aims of the present text are to explore the role played by the field of political economy scientific production as a relevant contribution to foster the debate about contemporary societies’ Renaissance phenomena, at the level of the prevailing cosmogonies that condition political action and thought. The institutional economics school of thought addresses social relations and intersubjectivity as structuring instances that condition what is and what is not possible to be thought, conceived, acknowledged and acted upon. Open inquiry research methodologies help to address the profusion of meanings that emerge from present turbulent contexts. Death and decay are part of living systems natural cycles, giving rise to new forms of growth and to new modes of existence. Modernity and Ancient thought, in Western cultures, created a separation between cosmogonies and Cosmo visions that reject or else that accept determinism and fatalism. Kairos, understood as the quality and existential experience of the passage of time, as opposed to Chronos, the quantitative and sequential idea of time, are critical to contrast deterministic influences. The crucial issue is that both Kairos and Chronos, both Modernity and Antiquity, and also both deterministic and non-deterministic influences help to explain how crises, individual and collective, institutional and civilizational, and local and global, give rise to novelty, to emergence and to renewal. Such renaissance effect is present in current times.